If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x=12x-6
We move all terms to the left:
11x-(12x-6)=0
We get rid of parentheses
11x-12x+6=0
We add all the numbers together, and all the variables
-1x+6=0
We move all terms containing x to the left, all other terms to the right
-x=-6
x=-6/-1
x=+6
| 3(4x-2)=4(3x-1) | | 3/8c=10 | | -3(x+2)=x | | 0.8x-1.6=1.2x-3.2 | | 11x-6x+204=11x+102 | | 5(n-2)-14n=-3n-(5-1n) | | 4a–4=2a+10 | | 6x-4(3x+8)=1 | | 0=2x^+6x+4 | | 13/8=k+1/2 | | 2x+1=1050-x | | 0.03r+0.025(1000-r)=27.25 | | ∠A=(5x-48)°,∠B=(3x+20)° | | 3(2+V)-4v=16 | | 1/5x+1/3=3 | | 13/3=k+1/2 | | 9n^2+360=0 | | Y=36+13x | | 2x+29=8(x+1) | | 2x^=6x=4 | | 6(8k+5)(k+7)=0 | | 4y-3=-5y+7 | | 10k=-2k | | 0.6(x-6)=7.8 | | 11/14x+1/2-3/7x=x-3/2x | | 1/4x+1/5=-4 | | ƒ(x)=-2x+3 | | 9/14=x/6 | | 150m-75m+48,250=51,000-175m | | 5x+17+15=x= | | 15x=12x+15=180 | | 1.5x+6=5 |